Determinants of students' academic performance in Corporate Governance I - Shamsoodien,Sihaam (College of Accounting, 2023)
With the increasing diversity of students attending university, there is a growing interest in the factors predicting academic performance. The objective of this study is to identify student endogenous factors (average Grade 12 grade, Grade 12 mathematics grade, Grade 12 English grade, gender, school quintile, home language, race, university gradepoint-average (GPA), university Accounting I grade and self-efficacy) that impact performance in the module, Corporate Governance I, and to identify any differences in self-efficacy levels of students of different genders and races completing this course. A quantitative research method was used, comprising multiple regression analysis, a Mann-Whitney U test and a Kruskal-Wallis H test. The data was obtained from a sample of students attempting Corporate Governance I in 2018 at the University of Cape Town. The findings indicate that on the first day of entering university, the average grade in the final year of high school was the most significant predictor of final performance in Corporate Governance I. GPA was the most significant predictor of performance at the point of registration for Corporate Governance I, before the student had embarked upon the course, as well as the point when the student had engaged with the course for a few weeks. Another interesting finding was that even though there were no significant statistical differences in the self-efficacy levels of students of different genders and races, females outperformed males while White students outperformed Black and Coloured students. This study adds to the existing literature on student performance in tertiary accounting programmes in South Africa with a particular focus on student endogenous factors. The findings could be useful for the University of Cape Town in determining its approach to teaching these students.